Kajian Yuridis Tindak Pidana Pencurian Dengan Pemberatan - Bahtiar, Bahtiar; Natsir, Muh.; Balla, Herman (Jurnal Litigasi Amsir, 2023)
This research was conducted with the following objectives to find out the application of material criminal law to the crime of theft by weighting in Decision Number: 263/Pid.B/2021/PN.PIN; and for the judge’s consideration in deciding on the crime of theft with a weight in Decision Number: 263/Pid.B/2021/PN.PIN. The type of research used in this paper is the type of research used is Normative Legal Research which is legal research conducted by examining library materials or secondary data. Normative legal research is also known as doctrinal legal research. The results of the study: 1. The application of material criminal law by judges to Article 363 paragraph (1) to 4 of the Criminal Code in conjunction with Article 65 paragraph (1) of the Criminal Code. Where the actions and the elements of the Article match each other; 2. Legal considerations by the judge regarding accountability for the actions committed by the defendant with the consideration that at the time of committing his actions, the defendant was aware of the consequences, apart from the above, the judge also did not see any justification or excuses that could eliminate the unlawful nature of the act. Defendant.